Picturing Our World : Contemporary Images of the Western Cape. - Dakawa Art & Craft Project, Grahamstown; Standard Bank Centre Gallery, Johannesburg; South African National Gallery, Cape Town (Cape Town : The South African National Gallery, 1993)
Appollis, Tyrone ; Atkinson, Kevin ; Baholo, Richard ; Bauer, Derek ; Bester, Willie ; Botha, Hardy ; Brand, Kevin ; Budaza, Hamilton ; Cape Mural Collective ; Cap Media Project ; Cheifitz, Jann ; Comerford, Jonathan ; Davids, Abraham ; etc.
Picturing Our World : Contemporary Images of the Western Cape, Dakawa Art & Craft Project, Grahamstown, 1.7.1993 - 11.7.1993 / Standard Bank Centre Gallery, Johannesburg, 3.8.1993 - 26.8.1993 / South African National Gallery, Cape Town, 23.9.1993 - 31.10.1993
boek